Barriers to Arabic Language Teaching in Higher Education Institutions in Malaysia: Realities and Solutions Based on Empirical Experience - Mohamed Rady Mohamed Elpaz Elsheakh; Mohd Syauqi bin Arshad (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2024)
Purpose – This study aims to identify the primary obstacles in teaching Arabic at higher education institutions in Malaysia and propose practical and effective solutions based on empirical experience. Arabic plays a crucial role in the educational context of countries with significant Muslim populations like Malaysia. This research is relevant for enhancing the quality of Arabic language teaching and enriching knowledge and cross-cultural communication skills. Design/methods/approach– The research employs an intrinsic case study approach at Sultan Abdul Halim Mu'adzam Shah International Islamic University, involving participants comprising lecturers, students, and academic staff engaged in Arabic language teaching. Data were collected through in-depth interviews, observations, and document analysis, and subsequently analyzed using thematic analysis techniques. Findings – The findings reveal several key obstacles in teaching Arabic, including teacher-centered instructional models, inadequate use of interactive media and teaching aids, limited reading materials, restricted opportunities for communication in Arabic, and non-conducive learning environments. Additionally, low student motivation emerged as a significant challenge.The study proposes several solutions, such as the development of more interactive teaching methods, increased utilization of technology in learning, provision of supplementary reading materials, and the creation of more conducive learning environments. These solutions are expected to enhance the quality of Arabic language teaching in Malaysia and help students achieve better language proficiency Research implications – The primary contribution of this research lies in offering a holistic approach that combines theoretical analysis and empirical data based on practical experience, providing more realistic and applicable guidance for Arabic language educators and education policymakers in Malaysia.